MdHB-7 Regulates Water Use Efficiency in Transgenic Apple (Malus domestica) Under Long-Term Moderate Water Deficit - Zhao, Shuang; Gao, Hanbing; Jia, Xumei; Wei, Jiangtong; Mao, Ke; Ma, Fengwang (Frontiers in Plant Science, 2021)
Improved water use efficiency (WUE) promotes plant survival and crop yield under water deficit conditions. Although the plant-specific HD-Zip I transcription factors have important roles in plant adaptation to various abiotic stresses, including water deficit, their functions in regulating WUE of apple (Malus domestica) are poorly understood. We characterized the role of MdHB-7 in WUE regulation by subjecting MdHB-7 transgenic plants to long-term moderate soil water deficit. The long-term WUE (WUEL) of transgenic apple plants with MdHB-7 overexpression or MdHB-7 RNA interference (RNAi) differed significantly from that of control plants. Upregulation of MdHB-7 caused reduced stomatal density, whereas suppression of MdHB-7 increased stomatal density under both normal and long-term moderate soil water deficit conditions. Moderate reduction in stomatal density helped to improve the WUE of of MdHB-7 overexpression transgenic plants, especially under water deficit conditions. MdHB-7 overexpression plants maintained high rates of photosynthesis that were conducive to the accumulation of biomass and the improvement of WUEL. MdHB-7 overexpression also alleviated the inhibition of root growth caused by long-term moderate soil water deficit and improved root vitality and hydraulic conductivity, which were essential for improving plant WUEL. By contrast, MdHB-7 RNA interference reduced the WUEL of transgenic plants by inhibiting these factors under normal and long-term moderate soil water deficit conditions. Taken together, our results provide solid evidence for a crucial role of MdHB-7 in the regulation of apple WUEL and provide new insights for improving the WUE of apple plants under moderate soil water deficit.